Transaksi Keuangan Mencurigakan dari Uang Elektronik Pada Masa Pandemi Covid-19: Suspicious Financial Transactions from Electronic Money During the Covid-19 Pandemic - Ginting, Yuni Priskila; Indradewi, Astrid Athina (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The development of technology in the era of globalization accompanied by lifestyle changes has brought a lot of influence in the human civilization system. Especially in the field of economics, which originally only used banknotes or cash to transact is now available some merchants, e-commerce, and online transportation as a provider of digital payment instruments that offer the use of electronic money. During the coronavirus disease 19 or Covid-19 pandemic, there is also an increasing trend towards electronic money transactions. Due to the emergence of the Covid-19 virus, the World Health Organization warned that banknotes may be able to spread coronavirus. This electronic money is very easy to transfer or transfer. This then raises a question about the possibility of money laundering crimes with increasing electronic money transactions during the covid-19 pandemic. The type of research used is Normative Juridical by conducting library studies that use various legal theories and laws and regulations. The problem approaches that the author takes are statutes approach and doctrinal approach. Transactions through electronics are prioritized during pandemics whose settings have not been specifically regulated coupled with the modus operandi that existed during the pandemic. Nevertheless, it remains attached to criminal responsibility for perpetrators of money laundering crimes. In this case, harmonization and cooperation between institutions are needed to be able to monitor and eradicate suspicious financial transactions.